Reservoir Rock Properties of the Upper Cretaceous Shiranish Formation in Taq Taq Oilfield, Iraqi Kurdistan Region - Baban, Dler H.; Qadir, Fuad M.; Mohammed, Aram R. (Sulaimani Journal for Pure and Applied Sciences, 2020)
Reservoir rock properties of the tight carbonate of Upper Cretaceous Shiranish Formation was studied in three selected wells in Taq Taq Oilfield/ Iraqi Kurdistan Region. The penetrated thickness of the formation by the studied wells of TT-04, TT-20, and TT-21 were 249, 290.8, and 236m respectively. The available logs and core test data were mainly dependant in characterizing the formation. The dominant limestone lithology of the formation was identified using Neutron-Density and M-N crossplots. The shale content, as calculated from the Gamma ray log, appeared to be highest in the lower part of the formation with about 15-30%. The shale content of Shiranish Formation are mainly consists of Glauconite, Illite, and Micas with a little contribution from other kinds of clay minerals like Montmorillonite. The total porosity of Shiranish Formation is generally less than 10% whereas the lower part of the formation has the lowest porosity (less than 5%). The calculated permeability through Multiple Regression Analysis method and by using the available core test data showed that The formation is generally of less than 10mD permeability. The lower part of the formation (at the two wells of TT-20 and TT-21) has relatively higher permeability compared to the middle and upper part of the formation. Three distinctive reservoir units were identified in this study in Shiranish Formation depending on variations in the shale content, porosity, and permeability. Reservoir unit (RU-1) at the upper part of the formation in the well TT-21is considered to be of the best reservoir property among the identified reservoir units in the three studied wells. The expected contribution of minor and large fractures in enhancing the permeability of the formation approved through output of the existed Formation Micro Image log for the lower part of the formation in the well TT-21.
Keywords: Shiranish Formation; Taq Taq Oilfield; Reservoir Units; Petrophysics